SEPARATION OF ETHANOL-WATER AZEOTROPE MIXTURES USING EXTRACTIVE DISTILLATION METHOD - Muhammad Ikhsan Taipabu; Wei Wu; Karthickeyan Viswanathana; Nikmans Hattu; Ervina Rumpakwakra; Micky Kololu (ALE Proceeding, 2023)
Extractive distillation is a specialized distillation process that involves adding an additional component (extractive agent or solvent/entrainer) to the mixture in order to alter the relative volatilities of the components and enable their separation, even when they form azeotropes. This technique is commonly used to separate azeotropic mixtures, such as ethanol-water azeotropes. The ethanol-water azeotrope is a well-known example, where the mixture contains around 95.6 wt% ethanol and 4.4 wt% water. Traditional distillation methods cannot separate these components efficiently due to the azeotropic behavior. However, extractive distillation offers a solution by introducing a third component (entrainer) that forms a ternary azeotrope, which has different properties compared to the binary azeotrope (ethanol-water). This study presents the effect of the operating parameters (e.g., column configuration, pressure, entrainer type) on energy consumption while the purity of ethanol is set to 99.5 wt%. Appropriate entrainers (i.e., glycerol, ethylene glycol) are chosen to extract water from methanol at different compositions. The optimum design of ethanol-water azeotrope separation is obtained by using sensitivity analysis in Aspen Plus simulation. The results indicate the trade-off between solvent and reboiler duty consumption. An advanced comparison study is recommended, including the mixing of both solvents as entrainer.